Innovative capacity building strategies for sustainable disaster risk management: A systematic review, conceptual framework, and future research directions - Saputra Nika; Ekha Putera Roni; Zetra Aidinil; Azwar (E3S Web of Conferences)
This systematic review examines innovative strategies for capacity building in sustainable disaster risk management (DRM). A review of 63 peer-reviewed articles, published between 2010 and 2024, was conducted using Scopus. The articles were analyzed to identify key themes related to technological innovations, community initiatives, and interdisciplinary approaches. Findings show that advancements in machine learning, Geographic Information Systems (GIS), and Information and Communication Technologies (ICT) significantly enhance DRM, particularly in risk assessment, early warning systems, and disaster response. Policy frameworks and institutional support were identified as critical to scaling and sustaining capacity-building programs. Community engagement, leveraging local knowledge, was also vital for ensuring the relevance and sustainability of these efforts. Interdisciplinary collaboration across government, NGOs, and the private sector further improved the effectiveness of these strategies. The study concludes that these efforts contribute to better disaster preparedness, increased resilience, and support sustainable development. This framework offers valuable insights for policymakers and practitioners looking to implement and scale innovative capacity-building strategies to improve global disaster resilience.